Review the impact of nanoparticles on the thermodynamics and kinetics of gas hydrate formation - Nashed, O. (Elsevier B.V., 2018)
Gas hydrates have been considered as a promising approach for gas separation, storage, and transportation. However, there are inherent restrictions that hinder this technique for commercialization such as slow hydrate formation, severe gas hydrate formation conditions, and limited storage capacity. Kinetic hydrate promoters are used to incorporate more gas into the liquid phase in order to enhance the hydrate formation process. This comprehensive review sheds light on the use of nanomaterial for gas hydrate promotion and relevant kinetic parameters. This review also addresses the factors that might rule the performance of nanofluids as promoters. Â© 2018 Elsevier B.V.